A Rare Complex BRAF Mutation Involving Codon V600 and K601 in Primary Cutaneous Melanoma: Case Report - Consoli, Francesca; Barbieri, Gianluca; Picciolini, Matteo; Medicina, Daniela; Bugatti, Mattia; Tovazzi, Valeria; Liserre, Barbara; Zambelli, Claudia; Zorzi, Fausto; Berruti, Alfredo; Giurisato, Emanuele; Vermi, William (Frontiers in Oncology, 2020)
BRAF is one of the most common mutated kinases detected in human cancer, particularly in cases of primary cutaneous melanomas (PCM). Mutations of the BRAF proto-oncogene, at the p.V600 codon, has been detected in more than 50% of primary and metastatic melanoma cells in clinical samples. These mutations lead to constitutive signal transduction in the MAPK (mitogen activating proteins kinase) pathway. This signaling pathway can be modified and reversed by the introduction of a combination of highly selective BRAF and MEK inhibitors in BRAFV600 mutated melanomas. In addition to the most frequent BRAF p.V600E mutation, corresponding to the single base pair substitution c.1799T>A, rarer mutations, within and outside the V600 codon, have been described. Expectedly, BRAF and MEK inhibitors (or their combination) have been poorly explored as potential therapeutic strategies in metastatic melanomas harboring this rare mutation. This work reports the genomic and clinical features of two melanoma patients showing a rare complex mutation affecting codon V600 and K601 of the BRAF gene, leading to a V600E2; K601I change. Specifically, these two patients show a distinct clinical behavior and significantly differ in their responses to BRAF and MEK inhibitors. The variability, it is proposed here, resulted as a direct consequence of the baseline extent of brain involvement, intracranial treatment failure as well as on the PTEN status.